2017
DOI: 10.1530/rep-16-0644
|View full text |Cite|
|
Sign up to set email alerts
|

Methylation dynamics during folliculogenesis and early embryo development in sheep

Abstract: Genome-wide DNA methylation reprogramming occurs during mammalian gametogenesis and early embryogenesis. Post-fertilization demethylation of paternal and maternal genomes is considered to occur by an active and passive mechanism respectively, in most mammals but sheep; in this species no loss of methylation was observed in either pronucleus. Post-fertilization reprogramming relies on methylating and demethylating enzymes and co-factors that are stored during oocyte growth, concurrently with the re-methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 71 publications
2
14
1
Order By: Relevance
“…The accumulation of transcripts during oocyte growth occurs during follicle recruitment, it is thus likely affected by the different hormonal status encountered during initial or cyclic recruitment. In accordance, abundant literature sustains the cytoplasmic immaturity of prepubertal oocytes in terms of abundance of specific transcripts (Bebbere et al, 2014;Bernal-Ulloa et al, 2016;Leoni et al, 2007;Masala et al, 2017;Oropeza, Wrenzycki, Herrmann, Hadeler, & Niemann, 2004).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The accumulation of transcripts during oocyte growth occurs during follicle recruitment, it is thus likely affected by the different hormonal status encountered during initial or cyclic recruitment. In accordance, abundant literature sustains the cytoplasmic immaturity of prepubertal oocytes in terms of abundance of specific transcripts (Bebbere et al, 2014;Bernal-Ulloa et al, 2016;Leoni et al, 2007;Masala et al, 2017;Oropeza, Wrenzycki, Herrmann, Hadeler, & Niemann, 2004).…”
Section: Introductionmentioning
confidence: 56%
“…The efforts in identifying the reasons for the reduced developmental competence not only improved the rates of embryo production from prepubertal donors (Earl, Irvine, Kelly, Rowe, & Armstrong, 1995;Ledda et al, 1999), but interestingly shed light into numerous aspects involved in oocyte potential. Morphological, cellular, biochemical and molecular studies confirmed the differential competence of gametes derived from adult and prepubertal donors in terms of resistance to cryopreservation (Leoni et al, 2006), metabolism and ultrastructure (O'Brien, Dwarte, Ryan, Maxwell, & Evans, 1996), transcript abundance (Bebbere et al, 2014;Ledda et al, 2012;Leoni et al, 2007;Romar et al, 2011), in vitro developmental competence and kinetics (Landry et al, 2016;Leoni et al, 2006Leoni et al, , 2015Majerus et al, 1999), mitochondrial distribution (Leoni et al, 2015) and methylation dynamics (Masala et al, 2017). Although the differential model has become a useful research tool independently on its breeding application, the limited competence of prepubertal oocytes is yet not fully understood.…”
Section: Introductionmentioning
confidence: 83%
“…Oocytes were then incubated with a primary antibody against 5MeC (mouse monoclonal Calbiochem NA81, EMD Biosciences, Inc., La Jolla, CA; 1:500 dilution) for one hour at room temperature in a humidified chamber. Primary antibody specificity was previously validated by other groups (Rougier et al, 1998;Mayer et al, 2000;Barton et al, 2001;Masala et al, 2017;Salmina et al, 2017). Following washes in blocking solution, samples were stained with secondary antibody (Alexafluor 555 rabbit anti-mouse, Invitrogen, Grand Island, NY; 1:200 dilution) for 30 minutes at room temperature in a humidified chamber in the dark followed by extensive washing in blocking solution.…”
Section: Mecmentioning
confidence: 99%
“…DNA methylation and hydroxymethylation profiling in early embryos of domestic animals, including bovine (Dobbs et al, 2013 ), porcine (Cao et al, 2014 ; Lee K. et al, 2014 ), ovine (Jafarpour et al, 2017 ; Masala et al, 2017 ), and equine (Heras et al, 2017 ), have mainly been reported via immunochemistry, separating 5mC and 5hmC at limited resolution. Although active demethylation is not observed in the maternal pronucleus, it has been reported in the paternal pronucleus of pig (Cao et al, 2014 ; Lee K. et al, 2014 ).…”
Section: MC and Tet-mediated Active Demethylation In Early Developmementioning
confidence: 99%
“…Both paternal and maternal pronuclei in bovine show 5hmC signal, despite a much less pronounced 5hmC level detected in the maternal pronucleus (Wossidlo et al, 2011 ; Bakhtari and Ross, 2014 ). Controversial data have been reported for ovine embryos (Jafarpour et al, 2017 ; Masala et al, 2017 ). Jafarpour et al reported a similar active-demethylation pattern between male and female pronucleus, i.e.…”
Section: MC and Tet-mediated Active Demethylation In Early Developmementioning
confidence: 99%